Corticomotor Plasticity Predicts Clinical Efficacy of Combined Neuromodulation and Cognitive Training in Alzheimer’s Disease - Brem, Anna-Katharine; Di Iorio, Riccardo; Fried, Peter J.; Oliveira-Maia, Albino J.; Marra, Camillo; Profice, Paolo; Quaranta, Davide; Schilberg, Lukas; Atkinson, Natasha J.; Seligson, Erica E.; Rossini, Paolo Maria; Pascual-Leone, Alvaro (Frontiers in Aging Neuroscience, 2020)
Objective: To investigate the efficacy of repetitive transcranial magnetic stimulation (rTMS) combined with cognitive training for treatment of cognitive symptoms in patients with Alzheimer’s Disease (AD). A secondary objective was to analyze associations between brain plasticity and cognitive effects of treatment. Methods: In this randomized, sham-controlled, multicenter clinical trial, 34 patients with AD were assigned to three experimental groups receiving 30 daily sessions of combinatory intervention. Participants in the real/real group (n=16) received 10Hz repetitive transcranial magnetic stimulation (rTMS) delivered separately to each of six cortical regions, interleaved with computerized cognitive training. Participants in the sham rTMS group (n=18) received sham rTMS combined with either real (sham/real group, n=10) or sham (sham/sham group, n=8) cognitive training. Effects of treatment on neuropsychological (primary outcome) and neurophysiological function were compared between the 3 treatment groups. These, as well as imaging measures of brain atrophy, were compared at baseline to 14 healthy controls (HC). Results: At baseline, patients with AD had worse cognition, cerebral atrophy, and TMS measures of cortico-motor reactivity, excitability, and plasticity than HC. The real/real group showed significant cognitive improvement compared to the sham/sham, but not the real/sham group. TMS-induced plasticity at baseline was predictive of post-intervention changes in cognition, and was modified across treatment, in association with changes of cognition. Interpretation: Combined rTMS and cognitive training may improve the cognitive status of AD patients, with TMS-induced cortical plasticity at baseline serving as predictor of therapeutic outcome for this intervention, and potential mechanism of action. Registered at ClinicalTrials.gov NCT01504958.